ADOMIAN DECOMPOSITION METHOD AND VARIATIONAL ITERATION METHOD FOR SOLVING SASA-SATSUMA EQUATION - Salih, Knier; Manaa, Saad (Science Journal of University of Zakho, 2025)
The Sasa-Satsuma equation is an integrable higher-order nonlinear Schrodinger equation. In this paper, two schemes are proposed to study numerical solutions of the Sasa-Satsuma nonlinear Schrödinger equation with initial conditions using the Adomian decomposition method and the variational iteration method. Both approaches produce quickly convergent series for each scheme with particularly important features. The present results have been displayed graphically and, in a table, to demonstrate the effectiveness and applicability of those techniques. The results obtained by the Adomian decomposition method are compared with the exact solution as well as the results obtained by variational iteration method. A comparison between the two approaches reveals that the Adomian decomposition approach is closer and more efficient than the variational iteration approach